Analytical and direct FE methods for free-field foundation modeling in 3D analysis of concrete dams - Abbasiverki, Roghayeh; Karami Mohammadi, Reza; Hariri-Ardebili, M. Amin (Frontiers in Built Environment, 2026)
Three-dimensional (3D) modeling is essential for reliable seismic assessment of concrete dams, as it captures canyon topography, monolith interactions, and joint nonlinearity that cannot be represented in two-dimensional (2D) analyses. This study systematically evaluates the seismic performance of a benchmark concrete gravity dam through comparative 3D and 2D finite element (FE) analyses, investigating two free-field foundation modeling approaches: (i) a direct FE method that explicitly accounts for canyon geometry, and (ii) an analytical approach employing simplified flat foundation assumptions. Using the domain reduction method, the nonlinear seismic analysis of the Pine Flat Dam implements effective earthquake forces as seismic input at the absorbing boundaries. The results reveal that while 2D analyses show methodological agreement (both relying on one-dimensional free-field assumptions), they fundamentally cannot reproduce 3D effects such as stress amplification from canyon geometry and monolith interactions. The direct FE method proves superior in predicting joint sliding and opening responses, as well as canyon amplification effects, whereas simplified approaches yield non-conservative estimates due to its failure to account for canyon-induced wave scattering. This study concludes that 2D modeling may be sufficient for preliminary analyses, but final design verification requires 3D simulation with direct FE free-field representation, particularly for dams located in irregular topographies.